1990
DOI: 10.1128/aem.56.1.230-236.1990
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of Recovery of Bdellovibrios from Brackish- Water Environments by Using Various Bacterial Species as Prey

Abstract: A total of 44 bacterial species subdivided into 10 trial experiments have been used as prey for the recovery of bdellovibrios from samples of water from a brackish tidal pond and an aquarium saltwater tank. In an initial investigation, the recovery efficiency of each of the test bacterial species was compared with that of a designated standard prey, Vibrio parahaemolyticus P-S. The results revealed that in each case strain P-5 yielded an equal or significantly greater number of plaques of bdellovibrios than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Bdellovibrio strains show prey specificity among various genera and species of gram-negative bacteria. Although, enteric bacteria are suitable target organisms, many bdellovibrios may not efficiently attack and lyse different bacterial species and serotypes (Fratamico and Whiting 1995;Schoeffield and Williams 1990;Starr and Stolp 1976). Bdellovibrio strains isolated from marine habitats require sodium chloride or sea water for growth.…”
Section: Members Of the Genusmentioning
confidence: 99%
See 2 more Smart Citations
“…Bdellovibrio strains show prey specificity among various genera and species of gram-negative bacteria. Although, enteric bacteria are suitable target organisms, many bdellovibrios may not efficiently attack and lyse different bacterial species and serotypes (Fratamico and Whiting 1995;Schoeffield and Williams 1990;Starr and Stolp 1976). Bdellovibrio strains isolated from marine habitats require sodium chloride or sea water for growth.…”
Section: Members Of the Genusmentioning
confidence: 99%
“…Bdellovibrios are capable of infecting and eventually causing lysis of a wide variety of gram-negative bacteria; however, the prey range susceptible to specific Bdellovibrio strains varies (Fratamico and Whiting 1995;Schoeffield and Williams 1990;Starr and Stolp 1976;Scherff 1973). Previous studies showed that the prey range of B. bacreriovorus 109J did not include E. cofi 0157:H7 and most Salmonella species tested in a two-membered system (Fratamico and Whiting 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SWYE plates (see recipe) Vibrio parahaemolyticus P-5 (Shoeffield and Williams, 1990) Sterile ocean water (see recipe) Polypeptone 20 (Pp) medium (see recipe) Pp top agar, molten (see recipe) Pp plates (see recipe) 28 • and 25 • C incubators Cell spreader, sterile 1. To SWYE plates, add 100 μl V. parahaemolyticus P-5 and spread evenly to distribute.…”
Section: Additional Materials (Also See Basic Protocol 1)mentioning
confidence: 99%
“…How Halobacteriovorax shapes saltwater microbial communities depends in part on which bacterial species are susceptible to predation by different Halobacteriovorax strains. Tests of Halobacteriovorax isolates from various saltwater environments indicate that, in general, this genus has a broad prey range [12, 13]. For example, predatory bacteria in saltwater aquarium and tidal pool samples attacked a phylogenetically diverse set of prey, including multiple species of Vibrio , Pseudomonas and E. coli [13].…”
Section: Introductionmentioning
confidence: 99%